Direct Estimation of the Surface Location of Immobilized Functional Groups for Concerted Catalysis Using a Probe Molecule. Issue 15 (25th February 2016) - Noda, Hiroto; Motokura, Ken; Wakabayashi, Yusuke; Sasaki, Kaori; Tajiri, Hiroo; Miyaji, Akimitsu; Yamaguchi, Sho; Baba, Toshihide
Abstract: The location of active sites during concerted catalysis by a metal complex and tertiary amine on a SiO2 surface is discussed based on the interaction between the functionalized SiO2 surface and a probe molecule, p ‐formyl phenylboronic acid. The interactions of the probe molecule with the surface functionalities, diamine ligand, and tertiary amine, were analyzed by FT‐IR and solid‐state 13 C and 11 B MAS NMR. For the catalyst exhibiting high 1, 4‐addition activity, the diamine ligand and tertiary amine base exist in closer proximity than in the catalyst with low activity. Abstract : Probing the surface : A novel technique using a probe molecule enables the measurement of active site distance for surface concerted catalysis; the relationship between catalytic activity and the immobilized metal complex–organic base distance on the SiO2 surface was clarified.